Sustainability or continuous damage: A behavior study of prosumers' electricity consumption after installing household distributed energy resources. (10th August 2020) - Li, Xingzhi; Lim, Ming K.; Ni, Du; Zhong, Bo; Xiao, Zhi; Hao, Haitian
Abstract: Household distributed energy resources (DER) have gained in popularity with the growing interest in environmental protection and with the technological development of internal combustion (IC) engines, gas turbines, microturbines, photovoltaics, fuel cells and wind power. It is understood that DER are able to reduce emissions by replacing fossil fuels with renewable energy sources. Meanwhile, there is no consensus regarding whether the installation of household DER increase or inhibit the use of electricity for original consumers. It is widely accepted that the installation of household DER should stimulate electricity consumption through more self-allocation. However, such conclusions are normally drawn based on linear regression models while ignoring certain important variables. After analyzing data from 409 households from 2016 to 2017 using an interactive regression model with human behavior indicators, contrary to the wildly accepted view that new technologies can have a rebound effect (RE), it is found that house DER not only facilitate environment protection in terms of limiting emissions but also inhibit electricity usage through a negative rebound effect. Highlights: Certain DER prosumers have a negative marginal rebound effect. Prosumers with different characteristics are influenced differently by DER. Rebound effects of DER are acceptable for promotion at lager scale.